The Advantages and Challenges of Electronic Exams: A Qualitative Research based on Shannon Entropy Technique - AHMAD KEYKHA; MASOOMEH IMANIPOUR; JAFAR SHAHROKHI; MOEIN AMIRI (Journal of Advances in Medical Education and Professionalism)
Introduction: The electronic exam is one of the foremost imperative instruments for evaluating students’ execution. Accordingly, this study aimed to identify the advantages and challenges of electronic exams based on Iranian and international studies.Methods: The present qualitative study used meta-synthesis in the first phase. Thus, keywords such as electronic exams, online exams, electronic assessment, and online assessment in Iranianand international databases for 2005-2021 were searched. In the second phase, using the Shannon entropy technique, the advantages and challenges of electronic exams were weighted.Results: Challenges of e-exams were classified into seven subcategories (poor technical knowledge, security challenges, complexity and challenges in designing examination, complexityand challenges during examination, complexity and challenges after examination, lack of infrastructure, socio-cultural challenges). The advantages of e-exams were also classified into five sub-categories, including improvement of teaching and learning process, effectiveness of student performance assessment, advantages in designing exams, advantages during examinations, and advantages after examinations. In Shannon’s entropy findings, challenges (complexity and challenges after examination and poor infrastructure) and advantages (advantage after exams implementation) had the largest weight.Conclusion: Considering the importance of electronic exams, especially with the outbreak of the COVID-19 epidemic, the inevitable movement of university systems, increasing concerns about student performance assessment, and improving educational performance in the current situation, decision-makers are expected to emphasize the advantages of this kind of exam and address its challenges to help improve the student assessment mechanisms.